2017
DOI: 10.1177/0009922817740666
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Children With Critical Bronchiolitis Living in Poor Communities

Abstract: There are established associations between adverse health outcomes and poverty, but little is known regarding these associations in critically ill children. We hypothesized that living in poorer communities would be associated with unfavorable outcomes in children with critical bronchiolitis. This retrospective study included children with bronchiolitis admitted to a pediatric intensive care unit (PICU) over a 2-year period. Median household income was estimated from patient ZIP codes and 2014 US Census Bureau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 38 publications
2
16
0
Order By: Relevance
“…Arabs in Israel generally have a lower socioeconomic status than do Jews, and more than 50% of the Arab population lives under the national poverty line [24]. Slain et al found that living in a poorer community (as expressed by a lower Federal Poverty Threshold) was significantly associated with longer PICU LOS, longer hospital LOS, higher odds of needing mechanical ventilation, and increased hospital charges in children with bronchiolitis [25].…”
Section: Discussionmentioning
confidence: 99%
“…Arabs in Israel generally have a lower socioeconomic status than do Jews, and more than 50% of the Arab population lives under the national poverty line [24]. Slain et al found that living in a poorer community (as expressed by a lower Federal Poverty Threshold) was significantly associated with longer PICU LOS, longer hospital LOS, higher odds of needing mechanical ventilation, and increased hospital charges in children with bronchiolitis [25].…”
Section: Discussionmentioning
confidence: 99%
“…9 This later subset of patients is termed to have "critical bronchiolitis." 10,11 The treatment of bronchiolitis is largely supportive, with evidence-based guidelines focusing on provision of fluids, comfort measures, and oxygen supplementation to correct hypoxemia. 12 Patients with critical bronchiolitis and acute respiratory failure, however, may require more advanced treatments, such as instrumentation with arterial or central venous catheters, inotropic and vasoactive infusions, noninvasive respiratory support, and mechanical ventilation.…”
Section: Introductionmentioning
confidence: 99%
“…Poverty is linked to adverse health outcomes across multiple pediatric conditions. [1][2][3][4][5][6][7][8][9][10] For the 13 million children currently growing up in poverty in the United States, the adverse exposures, heightened stress, and diminished access to healthpromoting resources that accompany a lower socioeconomic status negatively affect health and development through their entire lifetimes. [11][12][13][14] Socioeconomic disparities extend to pediatric critical illness.…”
mentioning
confidence: 99%
“…[11][12][13][14] Socioeconomic disparities extend to pediatric critical illness. Although the relationships between poverty and critical illness have not been thoroughly explored, available evidence suggests that children from lower-income families and communities are more likely to be admitted to the PICU because of both acute and chronic illnesses, 1,15 are more gravely ill at the time of admission, 15,16 and are more likely to die before PICU or hospital discharge. 17,18 We recently used the inpatient bedday (IPBD) rate to calculate and evaluate the burden of acute childhood illnesses across neighborhoods in our region.…”
mentioning
confidence: 99%